2021
DOI: 10.15345/iojes.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Examining Turkish Students' Views on the Reading Literacy Tasks of PISA 2018 in Terms of Different Variables

Abstract: The study investigates possible factors affecting Turkish students' perception of task difficulty in the Program for International Student Assessment (PISA) 2018. The research data consist of the survey responses of the students who participated in the PISA 2018. The participants include 6679 15-yearold Turkish students. The dependent variable of this study is the students' views of the reading task difficulty in the PISA 2018. Independent variables are divided into two as student-level and schoollevel variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Yet another study used hierarchical linear modeling (HLM) to investigate variables affecting reading literacy at both student and school levels and thereby revealed the effect of classroom climate (Ertem, 2020). Another study using HLM analysis revealed that the increase in school digital capacities makes it easier to perceive reading literacy tasks (Arı & Keskin, 2021). Ma, Luo, and Xiao (2021), who employed academic self-concept and academic enjoyment as mediating variables, revealed that perceived teacher support together with these variables affected reading literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another study used hierarchical linear modeling (HLM) to investigate variables affecting reading literacy at both student and school levels and thereby revealed the effect of classroom climate (Ertem, 2020). Another study using HLM analysis revealed that the increase in school digital capacities makes it easier to perceive reading literacy tasks (Arı & Keskin, 2021). Ma, Luo, and Xiao (2021), who employed academic self-concept and academic enjoyment as mediating variables, revealed that perceived teacher support together with these variables affected reading literacy.…”
Section: Introductionmentioning
confidence: 99%